2003
DOI: 10.1161/01.cir.0000091084.46500.bb
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Free Radical Release in Human Failing Myocardium Is Associated With Increased Activity of Rac1-GTPase and Represents a Target for Statin Treatment

Abstract: Background-Reactive oxygen species (ROS) contribute to the development of heart failure. A potential source of myocardial ROS is the NADPH oxidase, which is regulated by the small GTP-binding protein rac1. Isoprenylation of rac1 can be inhibited by statin therapy. Thus, we examined ROS and rac1 in human failing myocardium and tested their regulation by statins in vivo. Methods and Results-In human left ventricular myocardium from patients with ischemic cardiomyopathy (ICM) or dilated cardiomyopathy (DCM), NADP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
309
0
10

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 399 publications
(337 citation statements)
references
References 40 publications
18
309
0
10
Order By: Relevance
“…An increased cardiac expression of the NADPH oxidase subunits, NOX2 and p22 phox , was also reported after myocardial infarction both in an animal model (Fukui et al 2001) and in human myocardium (Krijnen et al 2003). Recently, our group and others confirmed that myocardium from end-stage human CHF patients demonstrates increased NADPH oxidase activity (Heymes et al 2003;Maack et al 2003).…”
Section: Involvement Of Nadph Oxidases In Lvh and Heart Failuresupporting
confidence: 60%
“…An increased cardiac expression of the NADPH oxidase subunits, NOX2 and p22 phox , was also reported after myocardial infarction both in an animal model (Fukui et al 2001) and in human myocardium (Krijnen et al 2003). Recently, our group and others confirmed that myocardium from end-stage human CHF patients demonstrates increased NADPH oxidase activity (Heymes et al 2003;Maack et al 2003).…”
Section: Involvement Of Nadph Oxidases In Lvh and Heart Failuresupporting
confidence: 60%
“…Insofar as statins inhibit isoprenylation of Rac1, these drugs also decrease the production of ROS. [11] Indeed, in rat models of heart failure treatment with statins was associated with decreased progression to heart failure after aortic banding. Importantly, simvastatin treated rats displayed lower tissue levels of superoxide anion production.…”
Section: Effect Of Statins On the Small G-proteins: Rho Rac And Rasmentioning
confidence: 99%
“…NADPH oxidase has been reported to possess a pivotal role as ROS origin in the failing myocardium of the patients with dilated or ischemic cardiomyopathy and the myocardium of the pressure-overloaded guinea pig. 25,26 Excess ROS, possibly from NADPH oxidase, can inhibit sarcoplasmic reticulum Ca 2ϩ uptake pump by irreversible direct oxidation of its thiol residue 27 or by impairment of the physiological phosphorylation of phospholamban. 28 The dual effects of ROS on intracellular Ca 2ϩ concentration might be involved in the mechanisms for ROS-induced cardiac dysfunction.…”
Section: Matsui Et Al Effect Of Potassium On Cardiac Function 227mentioning
confidence: 99%